PENINGKATAN HASIL BELAJAR PESERTA DIDIK MATERI KELILING BANGUN DATAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SDN 20 BEROK GUNUNG PANGILUN: Peningkatan Hasil Belajar - Tasha Wulandari Liandri; Fadila Suciana; Yullys Helsa; Refiona Andika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted in response to the low.learning outcomes of fifth-grade students on.the topic of perimeter and area of quadrilaterals at SDN 20 Berok Gunung Pangilun, caused by teacher-centered instruction and the limited use of effective learning models and media, which reduced student engagement and understanding. To address this issue, the Problem.Based Learning (PBL) model was implemented to promote active participation and develop students’ problem-solving skills, supported by Baamboozle as an interactive game-based learning medium to create a more engaging classroom environment. The purpose.of this study was to describe the improvement of students’ learning outcomes through the.application of the PBL model assisted by Baamboozle. This research employed Classroom.Action Research (CAR) with qualitative and quantitative.approaches conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages, involving 27 students. The results showed consistent improvement, with lesson planning (RPPM) increasing from 85% in cycle.I meeting 1 to 90% in meeting.2 and remaining stable at 90% in cycle II. Teacher.performance improved.from 87,5% to 89,28% and reached 96,42% in cycle II, while student activity increased from 85% to 89,28% and reached 96,42%. Students’ learning outcomes also improved, achieving an average score of 85,04 with.a mastery.level of 85,19% in cycle.II, indicating that the implementation of PBL assisted by Baamboozle effectively enhances learning quality and.outcomes.